Mechanisms mediating increased endurance following high- and low-load training with and without blood flow restriction - Chatlaong, M. A.; Mouser J. G.; Bentley, J. P.; Buckner, S. L.; Mattocks, K. T.; Dankel, S. J.; Loenneke, J. P.; Jessee, M. B. (Journal of Trainology, 2022)
Objectives: To determine if different mechanisms, i.e., changes in one-repetition maximum (1RM) strength (Delta1RM) or vascular conductance (DeltaVC), mediate changes in endurance (deltaEND) following training with 70% 1RM (70/0), 15% 1RM (15/0), and 15% 1RM with blood flow restriction using 40% (15/40) or 80% (15/80) arterial occlusion pressure. Design: Secondary analysis of data from a previous training intervention study. Method: Previously, 39 participants trained 2x/week for 8 weeks (4 sets of knee extensions to momentary failure) with 2 of the 4 aforementioned conditions (randomized, 1 per leg). VC, 1RM, and END were tested pre/post-training. A two-wave multiple-mediator model (adjusted for baseline values of 1RM, VC, and END) was constructed to evaluate direct and indirect effects of training on DeltaEND (relative to other conditions) with Delta1RM and DeltaVC as mediators. Results presented as coefficients (95%CI). Results: The model accounted for 35.3% (p < .001) of the variance in DeltaEND. Relative direct effects on DeltaEND did not differ across conditions (all p > .231). There was an effect of Delta1RM on DeltaEND [0.5 (0.0,0.9) repetitions] and evidence that Delta1RM mediated the effect on DeltaEND for 70/0 compared to other conditions [vs. 15/0 = 1.4 (0.1,2.9); 15/40 = 1.4 (0.1,2.7); 15/80 = 1.1 (0.1,2.3) repetitions]. There was no evidence of a relationship between DeltaVC and DeltaEND [0.02 (-0.10,0.13) repetitions] nor of relative indirect effects through DeltaVC when comparing conditions. Conclusions: Differences in delta1RM translate to increased endurance in the 70/0 condition compared to other conditions, however, differences in DeltaVC did not appear to mediate increased endurance across the conditions.